2007
DOI: 10.1016/j.bbrc.2007.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90—From signal transduction to cell transformation

Abstract: The molecular chaperone, Hsp90, facilitates the maturation and/or activation of over 100 'client proteins' involved in signal transduction and transcriptional regulation. Largely an enigma among the families of heat shock proteins, Hsp90 is central to processes broadly ranging from cell cycle regulation to cellular transformation. Here we review the contemporary body of knowledge regarding the biochemical mechanisms of Hsp90 and update the most current paradigms defining its involvement in both normal and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 60 publications
1
55
0
1
Order By: Relevance
“…This suggests a role for Hop in Hsp90-mediated inhibition of invasion through extracellular interactions. Hop acts as a co-chaperone in the Hsp90 chaperone cycle stabilising and activating a wide array of client proteins [30]. Having demonstrated that Hop knockdown resulted in decreased invasion through extracellular interaction with Hsp90 and MMP-2, we investigated whether siRNA knockdown of Hop could affect Hsp90-mediated client protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a role for Hop in Hsp90-mediated inhibition of invasion through extracellular interactions. Hop acts as a co-chaperone in the Hsp90 chaperone cycle stabilising and activating a wide array of client proteins [30]. Having demonstrated that Hop knockdown resulted in decreased invasion through extracellular interaction with Hsp90 and MMP-2, we investigated whether siRNA knockdown of Hop could affect Hsp90-mediated client protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate effective miRNA selection, we constructed reporter vectors for co-transfection with the miRNA vectors, by which effective miRNAs could be screened easily according to reduction of EGFPpositive cell numbers in the co-transfected cell cultures. Among seven candidate miRNAs tested using the reporter assay, five of them were shown to have significant inhibitory effects on cHsp90a or cHsp90b transcription, confirming the high reliability of the web-based siRNAdesign tool and our miRNA-expression system.The claim that cHsp90 is a functional component of the cellular receptor complex for IBDV binding is drawn from indirect evidence using an anti-human Hsp90a mAb (Lin et al, 2007); this cannot rule out the possibility of crossreactivity between cHsp90a and cHsp90b, as the two proteins are 85 % identical (Brown et al, 2007). Our stable transfection experiments showed that the anti-cHsp90a…”
mentioning
confidence: 90%
“…However, HSP90 is not capable of independent functionality as a protein chaperone, but requires the augmentation of its co-chaperones. HSP90 is crucial in signal transduction to transformation to genetic capacitance and infl uences a wide array of cellular events (Brown et al 2007). …”
Section: Hsp90 Classmentioning
confidence: 99%